Perceptions of Pregnant Mothers About Exclusive Breast Milk With The Motivation To Do Early Breastfeeding Initiation (IMD) at Klinik Ayah Bunda Kelurahan Amplas, Kecamatan Medan Amplas in 2021 - Yanti; Dwi Pratiwi Kasmara; Faradita Wahyuni (Pena Cendekia Insani, 2022)
Pregnancy is a natural and physiological process, making the mother happy later with the presence of the child being born. When the baby is born, it is placed directly on the mother's chest, where the baby will make physical contact with the mother, the baby will spontaneously look for the mother's nipple by itself, that's where the IMD process first occurs. Breast milk is a natural food for babies. According to the World Health Organization (WHO) exclusive breastfeeding at 6 months. In child survival worldwide, with child mortality nearly halving over two decades. The under-five mortality rate decreased by 49%, down from about 90 deaths. The purpose of this study was to determine the relationship between the perception of pregnant women about exclusive breastfeeding and the motivation to carry out Early Initiation of Breastfeeding (IMD). The study used an analytical survey research design method with a cross sectional approach. Data was collected by distributing questionnaires. The population in the study were 44 pregnant women at the Ayah Bunda Clinic. The sample in this study were mostly pregnant women, where the sampling technique was saturated sampling. Data analysis used Chi-square statistical test with 0.05. Based on the results of the research conducted, namely the relationship between pregnant women's perceptions of exclusive breastfeeding with motivation to initiate Early Breastfeeding with p (0.000) < (0.05) then Ha is accepted, meaning mothers with less perceptions will have low motivation later in providing IMD. From the results of this study, it is hoped that pregnant women will increase their knowledge and explore deeper information about exclusive breastfeeding and motivation to achieve success in carrying out Early Initiation of Breastfeeding (IMD).